Development of Vinpocetine-Loaded Nasal Polymeric Micelles via Nano-Spray-Drying - Bence Sipos; Gábor Katona; Flóra Mária Szarvas; Mária Budai-Szűcs; Rita Ambrus; Ildikó Csóka (MDPI AG, 2023)
In this present formulation study, vinpocetine-loaded nano-spray-dried polymeric micelles were developed via nano-spray-drying. Three different mucoadhesive excipients were applied in the studies, namely chitosan, hyaluronic acid and hydroxypropyl methylcellulose. In all cases, the formulations had a proper particle size and drug content after drying with spherical morphology and amorphous structure. After rapid dissolution in water, the polymeric micelles had a particle size around 100-130 nm, in monodisperse size distribution. The high encapsulation efficiency (>80%) and high solubilization (approx. 300-fold increase in thermodynamic solubility) contributed to rapid drug release (>80% in the first 15 min) and fast passive diffusion at simulated nasal conditions. The formulated prototype preparations fulfilled the demands of a low-viscosity, moderately mucoadhesive nasal drug delivery system, which may be capable of increasing the overall bioavailability of drugs administered via the auspicious nasal drug delivery route.